Jagged1 is Clinically Prognostic and Promotes Invasion of Glioma-Initiating Cells by Activating NF-κB(p65) Signaling - Long Hai (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Jagged1 is the ligands of the Notch signaling and has been shown to promote glioma-initiating cells (GICs) in glioblastoma. The role of Jagged1 in GICs invasion and underlying molecular mechanisms remain unclear. Methods: Survival data from R2 genomics analysis, the Cancer Genome Atlas (TCGA), the Chinese Glioma Genome Atlas (CGGA) and visualization platform database were used to evaluate the effects of Jagged1 on overall patient survival. we investigated Jagged1 induced the GICs cells’ invasion by matrix degradation assays and Transwell cell invasion assays in vitro, then we further explored the underlying molecular mechanisms using Co-immunoprecipitation (co-IP) analysis. Results: High expression of Jagged1 in human glioma was associated with poor survival. Clinical data analysis showed that the Jagged1 was positively correlated with NF-κB(p65). Jagged1-induced invasion of GICs cells through activation of NF-κB(p65) pathway. In vivo, knockdown of Jagged1 could suppress the tumorigenicity of GICs cells through NF-κB(p65) signaling. Conclusion: Insights gained from these findings suggest that Jagged1 plays an important oncogenic role in GICs malignancy by activation of NF-κB(p65) signaling, and Jagged1 could be employed as an effective therapeutic target for GICs.